Eksplorasi pengalaman dan dinamika coping pada korban Nonsuicide Self-Injury - Zulkifli, Indah Sari Dewi; Firdausiyyah, Kunti Zakiyyatal; 'Izzah, Nida Mukhlishotul (Universitas Muhammadiyah Malang, 2024)
Nonsuicidal self-injury (NSSI) is a mental health problem that has been found in many individuals entering adulthood. Atthis age, individuals are often considered unable to solve problems that lead to tendencies to anxiety or depression, nota few individuals choose to channel their emotions by hurting themselves with sharp objects. This study used qualitativemethods with phenomenological approaches and individuals as non-suicidal self-injury survivors as a unit of analysis.Participants in this study had age criteria of 18-25 years and one who had done NSSI in the last 6 months. Data collectiontechniques use interviews and observation. The results of the data analysis showed that the background of both subjectsdoing non-suicidal self-injury was due to the perceived pressure or stress experienced by both subjects. It was found thatto minimize NSSI behavior is to focus on emotional focused-coping including using emotional support, positive reframing,religion, and self-distraction.